(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Double-BSRs are enigmatic seismic data reflections with implications on subsurface fluid migration and phase, and hydrate stability in shallow subsea sediments. From 3D exploration seismic data, we detail the occurrence of a double BSR from the Offshore Niger Delta. Identified in an earlier study, we delineate the areal extent of the double-BSR and model expected temperatures at the deeper BSR to provide constraints on its origin. The deeper BSR occurs at a minimum estimated depth of 114 m below the upper BSR. Temperature modeling results indicate Structure I hydrates are unstable at the current depth of the deeper BSR. The lower seismic amplitudes and discontinuous nature of the deeper BSR and its apparent hinterland tilt relative to the upper BSR suggest it marked the base of the gas hydrate stability zone in the climatic (GHSZ) and tectonic past when the pressure-temperature (P-T) conditions were significantly different. We propose that recent tectonic uplift on the thrust-cored ridge system considerably altered local P-T conditions which led to the dissociation of gas hydrates and consequent upward migration of the base of the GHSZ to shallower levels until it reached its present state, leaving behind a tilted relic of its former position. The relic likely benefited from low advective rates which encouraged its preservation through time. We further reckon that the tilt of the Relict BSR relates to the rotation of the fold limb during recent thrust activity and as a result we aver that Relict BSRs may record limb rotation on fault-bend folds.